Wandering in strange lands : a daughter of the Great Migration reclaims her roots - Jerkins, Morgan (Harper, an imprint of HarperCollinsPublishers, 2020)
An acclaimed cultural critic presents the story of her journey to understand her northern and southern roots, the Great Migration, and the displacement of black people across America.